Reflections on the Gender-Higher Education Bond - Acuña-Rodríguez, María del Carmen (2014)
This is a theoretical and reflexive essay that expects to answer the question which role does the Higher Education has had in the dissemination of gender inequalities. To achieve this, three sections are developed. The first section, explores Higher Education and gender inequality according to a social perspective, where considerations such as how society is arranged in gender binary categories, and women’s situation in science and universities are addressed. The second section, Approaches for understanding the Gender-Higher Education bond, gives basic theoretical explanations about the gender approach, and mentions some Useful perspectives in order to analyze gender inequality in the tertiary level of education; in addition, it offers a brief reference about curricular design processes and intentions at universities. The third section, University curriculum, public policies and social change, refers to the importance Higher Education has in society, highlighting the development of public policies and the generation of social changes. As a conclusion, it affirms that it is possible to analyze the Gender-Higher Education bond upon theoretical references and available research. Women’s disadvantage in University is a reality that requires a social-cultural and structural change; to reach it, it is necessary to develop joint strategies and actions among diverse social agents, oriented to promote fair and equal actions between genders inside academy